Functional outcome of steroid injection in trigger finger between professional and service workers - Muhamad Syafiz Ahmad Ismani (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Trigger finger is one of the commonest causes of disabling hand pain in orthopaedics and affects individuals regardless of their daily activities. It is characterized by inflammatory changes in the retinacular sheath and peritendinous tissue at fibro-osseous tunnels which result in pain and triggering of the finger due to the discrepancy between the diameter of the flexor tendon and its sheath at the A1 pulley. This study aims to evaluate the degrees of responses of trigger finger upon steroid injection among professionals and service workers. An observational cohort study, evaluating the functional outcome of steroid injection among professionals and service workers according to the Green Classification and assessing the functional outcome using the Michigan Hand Outcomes Questionnaire (MHQ) in three separate visit; pre injection, post injection 6 and 12 weeks. The classification of professional and service group is according to the Malaysia Standard Classification of Occupation 2013 (MASCO). Both groups will undergo physiotherapy post steroid injection for optimum results. Forty four fingers in each group, with various stages of trigger finger underwent steroid injection. Overall MHQ score in both groups show a good functional outcome between pre injection and post injection at 12 weeks, (P values <0.001). Comparing the grades of trigger finger, the data analysis shows good functional outcome between pre injection and post injection at 12 weeks (P values <0.01) in both groups. There was only 1 (2.2%) patient in service group who underwent open release after the second visit following the steroid injection treatment. There are 7% of patients has hypopigmentation at the injection area. There is no serious complication been reported. Steroid injection is an excellent option of treatment trigger finger for professional and service workers allowing early return to work with no differences in outcome regardless of the stage. The treatment is shown to have a good functional outcome in both groups. We also concluded that extrasynovial/extrasheath inoculation of corticosteroid is adequate to yield remarkable results.